2016
DOI: 10.4049/jimmunol.1501176
|View full text |Cite
|
Sign up to set email alerts
|

Transient Surface CCR5 Expression by Naive CD8+ T Cells within Inflamed Lymph Nodes Is Dependent on High Endothelial Venule Interaction and Augments Th Cell–Dependent Memory Response

Abstract: In inflamed lymph nodes, Ag-specific CD4+ and CD8+ T cells encounter Ag-bearing DCs and, together, this complex enhances the release of CCL3 and CCL4 that facilitate additional interaction with naïve CD8+ T cells. While blocking CCL3 and CCL4 has no effect on primary CD8+ T cell responses, it dramatically impairs the development of memory CD8+ T cell upon Ag re-challenge. Despite the absence of detectable surface CCR5 expression on circulating native CD8+ T cells, these data imply that naïve CD8+ T cells are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
5
11
0
Order By: Relevance
“…Watanabe and colleagues showed that macrophages pretreated with CCL3 exhibit strengthened adhesion to osteoblasts leading to the formation of pre-osteoclast cells in vitro , an important step in the process of bone reabsorption ( 31 ). Previously, we showed that blocking CCL3 (and its paralog CCL4) in vivo decreased CD8 + T cell and DC contacts in the vaccine-draining LN and diminishes the magnitude of the overall CD8 + T cell memory pool ( 5 ). In two separate studies, Park and colleagues showed that pretreatment of DCs with CCL3 in combination with CCL19 and LPS stimulation led to enhanced OVA-specific CD4 + (OT-II) T cell proliferation in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Watanabe and colleagues showed that macrophages pretreated with CCL3 exhibit strengthened adhesion to osteoblasts leading to the formation of pre-osteoclast cells in vitro , an important step in the process of bone reabsorption ( 31 ). Previously, we showed that blocking CCL3 (and its paralog CCL4) in vivo decreased CD8 + T cell and DC contacts in the vaccine-draining LN and diminishes the magnitude of the overall CD8 + T cell memory pool ( 5 ). In two separate studies, Park and colleagues showed that pretreatment of DCs with CCL3 in combination with CCL19 and LPS stimulation led to enhanced OVA-specific CD4 + (OT-II) T cell proliferation in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Chemokines are cytokines that function primarily as chemoattractants and help maintain specific immune microenvironments by coordinating various immune cell–cell interactions in a specific spatio-temporal manner. For example, we and others have demonstrated a crucial role for CCL3 and CCL4 in maximizing chance encounters between naïve CCR5 + CD8 + T cells and dendritic cells (DCs) that undergo productive interactions with antigen (Ag)-specific CD4 + or CD8 + T cells in the LN draining vaccine sites ( 3 5 ). Furthermore, CCL3 has been shown to be required for maximal helper CD4 + T cell-dependent memory CD8 + T cell generation in the DLN during the initial T cell priming phase ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the AT and GA haplotypes of CCL4 are in LD with other functional polymorphisms that are responsible for the susceptibility to HCC. It has been reported that CCL4 secretion by CD4+- antigen-presenting cell APC complexes, which correlated with increased cross-priming of CCR5-expressing CD8+ T lymphocytes 32 . Then CD8+ T lymphocytes exit the draining lymph node and migrate to the tumor site, where they exert their cytotoxic function on cancer cells.…”
Section: Discussionmentioning
confidence: 93%
“…Elements located in the N-terminus and second ECL of CCR5 are specifically relevant for interactions with HIV-1 during virus entry, putting focus on them as attractive targets for designing more productive antiretroviral therapies. In addition, CCR5 has a further advantage as a cellular target because it is relatively unnecessary for normal immune function, in contrast with receptor CD4 and the viral coreceptor CXCR4 [17]. Both have critical roles in immune function [18,19], which severely limits their utility as antiretroviral therapy targets.…”
Section: Ccr5 Coreceptor As An Antiretroviral Target and The Delta 32 Mutationmentioning
confidence: 99%